Respuesta :

Answer:

x^3-x^2+1

Step-by-step explanation:

u(x)=x^5-x^4+x^2

v(x)=-x^2

(u/v)(x) = (x^5-x^4+x^2) /x^2

           = (x^5/x^2) - (x^4 /x^2) +(x^2/x^2)

            = x^(5-2) - x ^(4-2)+ x ^(2-2)

            =x^3-x^2+1

Answer:

[tex](u/v)(x)=-x^{3}+x^{2}-1[/tex]

Step-by-step explanation:

The arithmetic operation of the two equations presented in this case can be solved as a division of polynomials.

We can write the problem as:

[tex](u/v)(x)=\frac{u(x)}{v(x)} \\\\(u/v)(x)=\frac{x^5-x^4+x^2}{-x^2}[/tex]

We need not to forget the negative in the denominator. Then we can factor the numerator as follows:

[tex](u/v)(x)=\frac{(-x^2)(-x^3+x^2-1)}{(-x^2)}[/tex]

Now we can easily spot the solution, and get there with the following steps:

[tex](u/v)(x)=(\frac{-x^2}{-x^2}) (-x^3+x^2-1)\\\\(u/v)(x)=(1)(-x^3+x^2-1)[/tex]

As I said earlier we need to remember that the negative will change the symbols in the equation once we factor the polynomial.

And like that we get to the answer:

[tex](u/v)(x)=-x^{3}+x^{2}-1[/tex]